P09.04.B The importance of treatment tolerability for people with glioma: registry review and qualitative findings from the COBra Study. (5th September 2022) - Baddeley, E; Retzer, A; Sivell, S; Seddon, K; Bulbeck, H; Nelson, A; Adams, R; Grant, R; Watts, C; Aiyegbusi, O; Rivera, S; Kearns, P; et al.
Abstract: Background: Gliomas are the commonest form of primary brain tumour, accounting for 80% of malignant brain tumours. Gliomas represent a heterogeneous group of cancers with variable outcomes, traditionally graded from I to IV (least to most aggressive). The poor prognosis of some glioma patients and high symptom burden has led to a growing emphasis on their quality of survival. Maintaining cognitive function, physical function and other health-related quality of life aspects throughout the disease trajectory are key considerations, particularly for patients with aggressive forms of glioma. It is therefore important that glioma intervention studies collect data aligned with patient priorities that enables assessment of the net clinical benefit of treatments and facilitates informed decision-making. In particular, and of increasing recognition, is the importance of monitoring the incidence of adverse events during and after the course of an intervention, and understanding their impact upon patients, and patients' own assessment of, tolerability. Material and Methods: A trial registry review, a systematic review of the qualitative literature and semi-structured interviews with patients and caregivers were undertaken. Outcomes were extracted from these sources to formulate a longlist during the development of a core outcome set for glioma interventional trials (the COBra study). Results: The registry review (n=91), systematic review (n=21) and semi-structured interviews (n=19) identified many important outcomes and concepts, one of which was tolerability. Tolerability, adverse events, toxicity or safety was reported to be collected as an outcome in 46 trials. Outcomes related to tolerability were identified from 7 articles included in the systematic review. Themes related to tolerability emerged from the qualitative interviews. These included tolerability of side effects of treatment; trade-offs of side effects versus potential benefits in deciding on, and willingness to, undertake further treatment; and self-directed strategies for coping. Conclusion: There is a growing acknowledgement of the importance of treatment tolerability in the wider field of cancer research. In glioma research specifically, its significance is yet to be reflected in outcomes collected in trials. Our qualitative findings indicate tolerability is of high significance to patients and those close to them. Participants reported how their preconceptions and experience of tolerability influenced treatment decisions and treatment uptake. However, outcomes related to tolerability were collected in just over half of trials in our sample. Tolerability and items relating to the patients' experience of adverse events should be collected and reported in trial findings to reflect patients' priorities and enable informed treatment decisions.